Morphological and molecular identification of Trichoderma asperellum isolated from a dragon fruit farm in the southern Philippines and its pathogenicity against the larvae of the super worm, Zophobas morio (Fabricius, 1776) (Coleoptera: Tenebrionidae) - Rea Sebumpan; Kevin Rey Guiritan; Mayvel Suan; Christine Jean Abapo; Aashaq Hussain Bhat; Ricardo A. R. Machado; Prakaijan Nimkingrat; Nanette Hope Sumaya (Egyptian Journal of Biological Pest Control, 2022)
Abstract Background Trichoderma asperellum (Ascomycota: Hypocreaceae) is a globally recognized soil fungus due to its broad-spectrum antimicrobial and plant growth-promoting properties. To increase the availability of local strains, soil samples from a dragon fruit farm in Villanueva (Misamis Oriental, Philippines) were collected and baited using the insect-baiting technique. Results Using the baiting technique, T. asperellum strain, RMCK01, was isolated. The strain was characterized using morphological and molecular data and its biological control potential was tested using different conidial concentrations on the last larval instar of the super worm, Zophobas morio (Fabricius, 1776) (Coleoptera: Tenebrionidae). The ITS1 sequences of T. asperellum RMCK01 were 100% identical to the sequences of other T. asperellum isolates reported from Vietnam, India, Thailand, and China. In addition, T. asperellum RMCK01 was particularly efficient against Z. morio larvae. On day 21, 88.87%, 88.07%, and 86.73% of insects died when treated with a suspension containing 6 × 108, 3 × 109, and 2.68 × 107 conidia/ml, respectively. Conclusion The study highlights the potential of this fungal isolate as a biocontrol agent against insect pests.